The Impact of Mergers and Acquisitions on the Operating Performance of Acquiring Companies: The Case of Japan - Khaleel, MehnazTabassum (2020)
Mergers and acquisitions are perceived as one of the most significant investment decisions made by a firm. However, albeit the extensive empirical researches documenting the stock market return of firms around the announcement date, studies that analyse the operating performance of either the acquirer or the target are very limited especially for Japanese M&A market. This study aims to investigate the extent of value creation across the operating performance measures for the publicly listed acquiring firms in Japan. This study is based on 135 completed M&A transactions undertaken between January 1, 2007 and December 31, 2016. Based on my findings it can be inferred that the operating performance of the acquiring firms measured by four categories of indicators including accrual performance (return on assets, gross profit margin and net profit margin), cash flow performance (cash flow return on sales), solvency measures (debt equity ratio) and growth opportunity (sales growth) consistently reveal either declines or no significant improvements in operating performance following a merger or an acquisition.